Kontra-Preventif Peraturan Pemerintah Nomor 28 Tahun 2024 dalam Menangani Kesehatan Reproduksi Anak Usia Sekolah - Firdaus, Alfian Firdaus; Imron Mustofa (Majelis: Jurnal Hukum Indonesia, 2025)
Indonesia's rapid population growth, particularly among adolescents, has raised concerns regarding its social and reproductive health implications, including rising rates of unintended pregnancies, premarital sexual activity, and the spread of sexually transmitted infections (STIs). In response to these issues, the government issued Government Regulation (GR) No. 28 of 2024 as a derivative of Law No. 17 of 2023 on Health. One of its provisions regulates the provision of contraceptives for school-aged children and adolescents. This study aims to examine the implications of this provision in relation to religious values, social morality, and the direction of national health policy. The research employs a normative qualitative approach using juridical-philosophical analysis, along with an assessment of public responses, religious leaders’ perspectives, and the views of state institutions regarding the regulation. The findings indicate that Article 103 paragraph (4) letter e has sparked controversy due to the use of the term "provision," which is perceived as ambiguous and contradictory to religious norms particularly Islamic teachings and is viewed as potentially legitimizing premarital sexual behavior among students. These findings highlight the necessity for the government to reassess regulations that conflict with religious and local cultural values. Furthermore, the study advocates for strengthening preventive reproductive health education grounded in religious and moral principles, rather than directly providing contraceptives within school settings.